Высокостабильные волноводные полосно-пропускающие фильтры с расширенным диапазоном перестройки - Дубровка, Ф.Ф.; Степаненко, П.Я.; Бердар, Н.Н.; Короцинский, А.А. (Технология и конструирование в электронной аппаратуре, 2003)
Предложен новый подход к построению волноводных программируемых механически перестраиваемых полосно-пропускающих фильтров, отличающихся стабильностью характеристик и постоянством полосы пропускания при перестройке в широком диапазоне частот. Представлены результаты теоретического исследования, проектирования, изготовления, настройки и испытания действующих образцов. Отличные характеристики разработанного фильтра открывают возможности создания принципиально новых передающих станций систем связи. A new approach to building tunable bandpass filters with near constant bandwidth all over a wide tuning frequency range has been proposed. The essence of the idea is in an successful combining inductive and capacitive discontinuities. An adequate mathematical model of the filter based on generalized scattering matrix, obtained by using the integral equation method for solving diffraction problems for single discontinuities, has been developed. A tunable bandpass C-band filter prototype with a near constant bandwidth 26 MHz in the tuning frequency range 13 % has been designed, constructed and tested. Due to a near constant bandwidth over wide tuning frequency range the developed programmable waveguide filters open new possibilities in realization high efficient and cost effective frequency tunable transmit stations for various telecommunication systems.